Arrival time mapping with 15O-gas PET for cerebrovascular steno-occlusive diseases: a comparative study with CT perfusion - Masanobu Ibaraki; Yuki Shinohara; Aya Watanabe; Kaoru Sato; Tomomi Ohmura; Hiroyuki Yamamoto; Toshibumi Kinoshita (EJNMMI Research)
Abstract Background Positron emission tomography (PET) with 15O-gas for quantifying cerebral blood flow (CBF) and oxygen metabolism is the gold standard for assessing hemodynamics in ischemic cerebrovascular disease. However, conventional 15O-gas PET methods do not provide information on regional arrival timing, a hemodynamic parameter typically measured using computed tomography (CT) perfusion with contrast media. This study demonstrated that 15O-gas PET with a state-of-the-art clinical PET scanner and optimized analysis can generate arrival time maps. In this retrospective study of ten patients with unilateral stenosis or occlusion of the major arteries, we compared PET-derived arrival time maps with CT perfusion Tmax maps. Results In PET with short inhalation of [15O]-CO2 gases, dynamic images were reconstructed with 2-sec temporal resolution, followed by weighted least-squares fitting of one-tissue compartment models, with or without the contributions from vascular components. PET arrival time maps were visually comparable to CT perfusion Tmax maps regarding the spatial extent of delayed brain regions, with less noise and higher image quality when using the model without the vascular components. Region-of-interest analyses showed good correlations between the two modalities: correlation coefficients of 0.834 for absolute values and 0.718 for ipsilateral-to-contralateral differences, respectively, indicating that 15O-gas PET can quantitatively measure the arrival time with reasonable accuracy. Conclusions The present method generates arrival-time maps with 15O-gas PET by applying optimized kinetic analysis to dynamic [15O]-CO2 images acquired using a state-of-the-art, high-sensitivity clinical PET scanner. Additional arrival time information for conventional PET parameters of CBF and oxygen metabolism may facilitate a more comprehensive understanding of the hemodynamic status in cerebrovascular steno-occlusive diseases.